Język i styl powieści pt. Pokraj Andrzeja Saramonowicza – rekonesans - WYRWAS, KATARZYNA (Stylistyka, 2024)
The article as a research reconnaissance contains an analysis of the language and style of Andrzej Saramonowicz’s novel Pokraj. The author discusses selected determinants of the original language of the novel, e.g., vocabulary, metaphors, comparisons, and significant proper names. Much attention was paid to intertextual references, such as the imitation of clearly recognisable forms (drama, film script, radio news, religious texts), recalling texts related to a common theme in the form of a collage and the use of quotes and paraphrases, the accurate reading of which depends on the cultural competence of the readers. The presented analyses show the author’s procedures that build a specific humour, serve criticism, parody, and satire.